Diversity of reactivity modes upon interplay between Au(iii)-bound isocyanides and cyclic nitrones: a theoretical consideration12. Issue 3 (21st December 2016) - Kuznetsov, Maxim L.; Kukushkin, Vadim Yu.
Abstract : The chemical diversity of the reactions between Au(iii )-bound isocyanides and cyclic nitrones was investigated by theoretical (DFT) methods. Abstract : Metal-bound isocyanides demonstrate a very rich chemistry towards 1, 3-dipoles of the allyl anion type such as nitrones. Depending on the metal centre, dipole nature and substituent in isocyanides, cycloadducts, imine + isocyanates or metallacycles may be formed. In this work, the reasons for such diversity, intimate details of the reaction mechanism and main factors determining the chemoselectivity in the reaction between Au(iii )-bound isocyanides ([AuCl3 (CNR)]) and cyclic nitrones − O–N̲ + C(H)XXX̲ (XXX = CH2 CH2 CMe2, CH2 CH2 CH2, OCH2 CMe2, CH2 OCMe2 and CH2 CH2 O) are analysed in detail by theoretical (DFT) methods. The formation of cycloadducts is controlled by the LUMOπ*(CN) of isocyanides and it occurs in a stepwise manner via the initial nucleophilic addition of nitrone at the C atom of CNR (except for nitronate − O–N̲ + C(H)CH2 CH2 O̲). The imine + isocyanate products are formed upon oxygen transfer from nitrones to isocyanides, and N–O bond cleavage is the main factor determining this process. A metallacycle is formed upon decomposition of the cycloadduct, and this process includes deprotonation of the oxadiazoline CH group/N–O bond cleavage and Cl − elimination/cyclization. The main factor controlling the metallacycle formation is the acidity of the endocyclic CH group in the cycloadduct. Effects of the substituent R in CNR and the nitrone nature on the reactivity are analysed.